Osobennosti razvitija psichomotornych kacestv junošej 12-14 let na nacal'nom etape sportivnoj podgotovki v karate - Zakharov, O. Yu.; Ermakov, P. N.; Bykov, N. N. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
Inclusion of karate in the program of the Olympic Games 2020 in Tokyo made this sport even more attractive that updated the preparation problem competitively of the capable sports reserve by the Olympic types of the program of karate: kata and kumite. The research objective: to reveal features of impact of the training process constructed on the basis of integration of features of traditional east pedagogics of training in complexes of the kata and the modern system of sports preparation on the organism of the athletes who are doing karate at the initial stage of sports preparation. In the research 37 youth karatekas, with the experience of sports preparation not less than one year, took part in the age period of 12-14 years. Motivation degreeto training process, speed of simple visually motor reaction, lability of nervous system, concentration of attention, ability to differentiation of kinematic and dynamic characteristics of the movement, random access figurative memory, strong-willed qualities were tested. In three years, athletes of experimental group (kata), in comparison with athletes of control group (kumite), had statistically reliable excess of indicators (in %): in speed of simple visually motor reaction on 2.8; concentration of attention on 21.8; abilities to differentiation of kinematic and dynamic characteristics of the movement on 31.8; random access memory on 35.0. At athletes of control group (kumite), statistically reliable excess of indicators in comparison with athletes of experimental group is noted: strong-willed qualities on 10.3, the maximum frequency of movements on 8.9. Change of the motivation exponent in athletes of both groups are statistically doubtful. Integration of features of traditionaleast pedagogics of training in complexes of the kata and the modern system of sports preparation is the perspective direction of improvement of training process for the athletes specializing in the kata.